Selection of Thai Medicinal Plants with Anti-Obesogenic Potential via In Vitro Methods - Wijitrapha Ruangaram; Eisuke Kato (MDPI AG, 2020)
The prevalence of obesity is increasing globally. Despite the availability of a variety of anti-obesogenic drugs, including therapies under clinical development, these treatments are often indicated for patients with severe obesity, making them unsuitable for patients with mild obesity or for preventative use. In Thailand, traditional remedies employing medicinal plants are widely used to maintain health and treat disease. These treatments are generally inexpensive and readily available at markets, making them good treatment options for preventing obesity. To evaluate the anti-obesogenic potential of Thai medicinal plants, we employed three in vitro methods: pancreatic lipase inhibition, lipolysis enhancement, and lipid accumulation reduction assays. Among 70 Thai medicinal plants, Eurycoma longifolia Jack, Tiliacora triandra Diels, and Acacia concinna (Willd.) DC. were selected as the most favorable candidates because they exhibited anti-obesogenic activity in all three assays. These medicinal plants are expected to have efficient anti-obesogenic effects, making them promising candidates for further study.